Depletion of licensing inhibitor geminin causes centrosome overduplication and mitotic defects - Tachibana, Kiku-e K (2005)
Metazoans limit origin firing to once per cell cycle by oscillations in cyclin-dependent kinases and the replication licensing inhibitor geminin. Geminin inhibits pre-replication complex assembly by preventing Cdt1 from recruiting the minichromosome maintenance proteins to chromatin. Geminin depletion results in genomic over-replication in Drosophila and human cell lines. Here, we show that loss of geminin affects other cell cycle-dependent events in addition to DNA replication. Geminin inactivation causes centrosome overduplication without passage through mitosis in human normal and cancer cells. Centrosomes are microtubule-organizing centres that are duplicated during S phase and have an important role in the fidelity of chromosome transmission by nucleating the mitotic spindle. Consistent with this, geminin-depleted cells show multiple mitotic defects, including multipolar spindles, when driven into mitosis by checkpoint abrogation. These results show that the consequences of geminin loss exceed its immediate role in DNA replication and extend to promoting chromosome mis-segregation in mitosis.